Quantitative evaluation and traceability analysis of concrete apparent shade and apparent uniformity - Jue Lu; Faguang Leng; Jingliang Xia; Jing Wang; Longfang Ren (Case Studies in Construction Materials, 2025)
Appearance quality serves as a comprehensive indicator of material homogeneity and construction quality. However, research on appearance quality traceability remains limited, especially regarding the influence of controllable factors during production. To address this gap, concrete was prepared using different mix proportions, formwork types, and release agents, with appearance images collected at specified curing ages. The average grayscale (Ave) and the coefficient of variation of grayscale (Cv) were employed as quantitative indicators for apparent shade and uniformity, respectively, using digital image processing techniques. Then, statistical analysis revealed that formwork type, release agent and curing age together explained the variation in apparent shade. Among these factors, only formwork was used to explain the change in apparent uniformity. Finally, through validity test, internal test, external test and residual analysis, the stability and prediction range of the models were confirmed. This method can be used for rapid batch screening, like initial inspection on construction sites.